2016
DOI: 10.5966/sctm.2016-0037
|View full text |Cite
|
Sign up to set email alerts
|

In Pursuit of Authenticity: Induced Pluripotent Stem Cell-Derived Retinal Pigment Epithelium for Clinical Applications

Abstract: For effective treatment, induced pluripotent stem cell (iPSC)-retinal pigment epithelium (RPE) must recapitulate the physiology of native human RPE cells. A set of physiologically relevant functional assays that assess the polarized functional activity and maturation state of the intact RPE monolayer is provided. The study data show that donor-to-donor variability exceeds the tissue-to-tissue variability for a given donor and provides, for the first time, criteria necessary to identify iPSC-RPE cells most suit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
77
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 87 publications
(83 citation statements)
references
References 61 publications
5
77
1
Order By: Relevance
“…Our observations suggest a clear involvement of genetic susceptibility towards AMD, notably in the inflammatory and complement factors associated with AMD pathogenesis. The tissue of origin (cornea or RPE) was not the same for all hiPSC-RPE lines which could result in some epigenetic differences; however, in a recent study, we found that such different originating tissues did not affect hiPSC-RPE phenotype or functionality (Miyagishima et al, 2016), and we found no significant differences related to tissue of origin or to cell passage. Some AMD-associated factors did not show significant differences between AMD and control lines, but these could emerge if oxidative stressors (Rabin et al, 2013) or complement components such as C1q (Johnson et al, 2011) or molecules that accelerate aging such as progerin (Miller et al, 2013) were added.…”
Section: Discussioncontrasting
confidence: 56%
“…Our observations suggest a clear involvement of genetic susceptibility towards AMD, notably in the inflammatory and complement factors associated with AMD pathogenesis. The tissue of origin (cornea or RPE) was not the same for all hiPSC-RPE lines which could result in some epigenetic differences; however, in a recent study, we found that such different originating tissues did not affect hiPSC-RPE phenotype or functionality (Miyagishima et al, 2016), and we found no significant differences related to tissue of origin or to cell passage. Some AMD-associated factors did not show significant differences between AMD and control lines, but these could emerge if oxidative stressors (Rabin et al, 2013) or complement components such as C1q (Johnson et al, 2011) or molecules that accelerate aging such as progerin (Miller et al, 2013) were added.…”
Section: Discussioncontrasting
confidence: 56%
“…Having diverse phenotypes in the training set enhanced the robustness of the algorithms, as was expected from the literature (18). Additionally, the method worked on 2 different donors, not only as an end-point assay of tissue health, but also as a noninvasive tool for tracking tissue development during the long maturation period (approximately 35 days) (33). Importantly, the accuracy of the algorithms in predicting both TER and VEGFratio was close to the measurement uncertainty for both TER (31) and VEGF (30,34).…”
Section: Discussionmentioning
confidence: 88%
“…However, much is still not understood about the genetic characteristics of stem cell‐derived RPE or its behavior after transplantation . Furthermore, there is only limited information about the functionality of ion channels and Ca 2+ signaling in stem cell‐derived RPE. In particular, studies about the voltage‐gated Ca 2+ (Ca V ) channels in these cells are lacking.…”
Section: Introductionmentioning
confidence: 99%